Hoshin kanri: policy management in Japanese subsidiaries based in Poland - Ćwiklicki, Marek; Obora, Hubert (Business, Management and Economics Engineering, 2011)
This article presents the findings from a research project on the Polish model of Hoshin Kanri identified in Japanese subsidiaries operating in Poland. It begins with an overview of the basic models of the method described in literature. Next, the findings of the project are presented. They were established on the basis of the first, quantitative stage of research conducted in over 50 enterprises of this kind and focusing on the awareness and practical application of Japanese management methods. The case studies permitted to develop a meta-model of the method typical of Japanese companies operating in Poland.